Extension of the ELECTRE II method to group decision-making - SAVADOGO, Zo¨ınabo; Koumbebare, KAMBIRE; ZARE, Sougoursi Jean Yves (International Journal of Applied Mathematical Research, 2023)
Multi-criteria decision support has long been treated in a single-decision maker framework . It seems that a decision made by a single decision-maker does not reflect reality . There are multi-criteria group decision support methods in the literature . In order to find a collective aggregation method fulfilling good properties , we have in this work , used the median and the quadratic mean to make the Extension of ELECTRE II (EE-II) to the group decision . We have made numerical applications and we have obtained interesting results .